Correlation of Neutrophil to Lymphocyte Ratio (NLR) Values to Ejection Fraction, Fraction Shortening, and E/A Ratio in Children with Rheumatic Heart Disease (RHD) at Dr. M. Djamil General Hospital, Padang, Indonesia - Farid I Hussein; Didik Hariyanto; Amirah Zatil Izzah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Monitoring the performance of the cardiac function is a must in monitoring patients with rheumatic heart disease (RHD). Echocardiography is the main diagnostic tool that plays a role in monitoring heart function, but the existence of this tool is only in tertiary health services and generally requires special expertise. This study aims to determine the correlation between the neutrophil to lymphocyte ratio (NLR) and markers of cardiac function performance on echocardiography, namely ejection fraction, fraction shortening, and E/A ratio in children with rheumatic heart disease at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This was an analytical observational study with a cross-sectional approach. A total of 34 subjects were included in this study. Data analysis using SPSS was univariate and bivariate, with p<0.05. Results: There was a correlation between the NLR value and the echocardiographic ejection fraction (EF) parameter (p>0.05) with a very weak correlation strength, while the correlation between the NLR value and the FS echocardiography parameter (p<0.05), the direction of the correlation formed is positive with a strong correlation weak (r=0.388). As for the correlation of NLR values with echocardiographic parameters E/A (p<0.05), the direction of the correlation formed was positive with a weak correlation strength (r=0.353). Conclusion: There is a weak correlation between NLR values with FS and E/A echocardiographic parameters and no correlation between NLR and EF echocardiographic parameters in rheumatic heart disease patients at Dr. M. Djamil General Hospital, Padang, Indonesia.